Color Mass in Artistic Expression: A Visual Art Analysis of Alisher Navoi’s Works - Qutliyeva Mahbuba Bekpulatovna (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This study examines the role of color mass in artistic expression within the works of Alisher Navoi, focusing on its visual and aesthetic functions. The research analyzes how color mass contributes to the creation of vivid imagery, compositional balance, and emotional resonance, as well as its pedagogical significance in art education. In Navoi’s works, color mass not only enhances the depiction of artistic scenes but also guides the viewer’s or reader’s perception, developing visual literacy and creative competencies. The study highlights both theoretical insights and practical applications of color mass for understanding literary and visual art interplay.